Disentangling Covid-19, economic mobility, and containment policy shocks - Annika Camehl; Malte Rieth (Halle Institute for Economic Research (IWH), 2021)
We study the dynamic impact of Covid-19, economic mobility, and containment policy shocks. We use Bayesian panel structural vector autoregressions with daily data for 44 countries, identified through sign and zero restrictions. Incidence and mobility shocks raise cases and deaths significantly for two months. Restrictive policy shocks lower mobility immediately, cases after one week, and deaths after three weeks. Non-pharmaceutical interventions explain half of the variation in mobility, cases, and deaths worldwide. These flattened the pandemic curve, while deepening the global mobility recession. The policy tradeoff is 1 p.p. less mobility per day for 9% fewer deaths after two months.
urn:nbn:de:gbv:3:2-134086
Keywords: C32; E32; I18; 330; Bayesian analysis; coronavirus; epidemics; general equilibrium; non-pharmaceutical interventions; panel data; structural vector autoregressions